Abdominal Tuberculosis Complicated by Intestinal Perforation - Michiel L. Sala; Samuel M. Verhage; Frank Zijta (Case Reports in Gastrointestinal Medicine)
Although relatively rare, there is an increasing incidence of abdominal tuberculosis (TB) in the developed countries, with the peritoneum being the most common site of involvement. Manifestation of abdominal TB should be considered in patients with relevant clinical symptoms and risk factors, including a history of prior TB infection and residence in or travel to an area where tuberculosis is endemic. We report a case of intestinal tuberculosis with a complicated disease course after the completion of treatment. Persisting abdominal symptoms during or after treatment should raise suspicion of subclinical intestinal obstruction. Early clinical recognition and surgical treatment may avoid poor outcome due to intestinal perforation.